An enriched 6-node MITC plate element for yield line analysis - Lee, Chi King (2014)
A 6-node triangular Reissner-Mindlin plate element with eXtended Finite Element Method (XFEM) formulation for yield line analyses is presented. The XFEM formulation with regularized enrichment is employed to reproduce a displacement field with a locally high gradient in the vicinity of a yield line in plate structures. The MITC technique is employed to mitigate shear locking in both the smooth and the locally non-smooth displacement fields. Several numerical examples are presented to illustrate the effectiveness of the XFEM enrichment in yield line analysis as well as the necessity and the effectiveness of the MITC technique in shear locking alleviation in the XFEM formulation.